ELLIPSOID REFLECTOR DESIGN TO USE IN ARCHITECTURAL LIGHTING - Ozturk, Leyla Dokuzer; Tong, Togan; Yagmur, Sensin Aydin (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2008)
The luminaire is the main tool to set up a lighting arrangement in an interior which provides the good visual conditions completely. The fundamental aim of luminaire design is to send the light of a lamp, emitting in almost all directions, in the desired directions. The control of lamp light is generally possible by reflection of light. Therefore, most luminaires include a reflector to direct the lamp light in the necessary directions and great importance is attached to reflector design in lighting. In order to obtain successful results in reflector design, controlling the features of the luminaire such as light intensity distribution, luminaire efficiency, illuminance distribution during the reflector design phase is important as well as forming the reflector shape according to the desired conditions. Curved and cylindrical reflector designs have been made to provide uniform illuminance distribution by using different point and linear light sources in the research project with the title Basic Principles and Recommendations on Reflector Design to Provide Uniform Illumination supported by TUBITAK. Light intensity distribution, luminaire efficiency of the luminaires containing the designed reflectors and the occurred illuminance distributions are determined with the help of a luminaire analyze and design program. In this study, the analyze results of ellipsoid reflectors are introduced.
Keywords: Reflector design; ellipsoid; uniform illuminance distribution; point light source; light intensity distribution; Architecture